Genetic predisposition for medication-related osteonecrosis of the jaws: a systematic review. Issue 10 (October 2019) - Sandro Pereira da Silva, J.; Pullano, E.; Raje, N.S.; Troulis, M.J.; August, M.
Abstract: The purpose of this study was to assess whether genetic variation is a predictor for the development of medication-related osteonecrosis of the jaws (MRONJ) in patients receiving bisphosphonate therapy for various conditions. A systematic review based on the PRISMA guidelines was performed. A search strategy was developed. Comprehensive searches of major databases were conducted for studies published January 2003 through July 2018. The PICOS strategy was used to develop the inclusion criteria. The analysis in each study was performed primarily using single nucleotide polymorphism (SNP) frequency mean values and odds ratios between cases and controls. A total of 3301 patients were enrolled in the 15 included studies (two genome-wide association studies, n  = 1877; 10 candidate gene studies, n  = 1195; three whole genome/whole exome studies, n  = 229). Multiple myeloma was the most prevalent primary disease (54.8%). Zoledronate was prescribed in 68.8% of patients. No one SNP was definitively identified as a risk factor for the development of MRONJ. To date, studies have failed to show a single gene as a risk factor for MRONJ. Heterogeneity of case and control populations may be contributory. Next generation sequencing studies may help elucidate the role and interplay of genetic events in the development of MRONJ.